Current State and Future of Investor-State Mediation (Polish Yearbook of International Law, 2025)
To protect the investments of their investors abroad, countries began to conclude investment treaties among themselves in the middle of the 20th century. The main feature of such treaties has been the availability of an effective mechanism for resolving disputes between a state and an investor. Most of them provide for arbitration, the effectiveness of which is universally recognised. However, arbitration has come under criticism in recent years. Among the main reasons are the inconsistency of awards, the high cost and long duration of proceedings, the lack of transparency and other issues. Due to that, practitioners and scholars call for reform and suggest, inter alia, resorting to investor–state mediation. In this regard, many developments have been made to increase the use of mediation in future. For example, the Working Group III reform is currently taking place, the Singapore Convention has been signed, arbitration rules and guidelines have been issued, etc.